2022
DOI: 10.3390/agronomy12122923
|View full text |Cite
|
Sign up to set email alerts
|

Selection of High Yield and Stable Maize Hybrids in Mega-Environments of Java Island, Indonesia

Abstract: Determination of grain yields of stable and high-yielding maize hybrids in a wide environment requires high accuracy. Many stability measurement methods have been used in multi-environment experiments. However, the relationships among the different methods are still difficult to understand. The objectives of this study were to 1. Identify the effect of growing season and location (Environments = E), hybrids (Genotypes = G), and their interactions (GEIs) on grain yields; 2. Select high-yielding and stable maize… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
26
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 13 publications
(29 citation statements)
references
References 45 publications
3
26
0
Order By: Relevance
“…The mean grain yield per hectare of maize grown during the dry season (7.76 ton ha -1 ) was higher than the average grain yield per hectare of maize grown during the rainy season (8.08 ton ha -1 ). These findings follow study findings by Yasin et al [48] and Wicaksana et al [23], which stated that grain yield per hectare of maize grown during the dry season was higher than those grown during the rainy season. The grain yield of maize is highly influenced by air temperature [49,50].…”
Section: Effects Of Genotype × Environment Interactions On Harvest Ag...supporting
confidence: 91%
See 1 more Smart Citation
“…The mean grain yield per hectare of maize grown during the dry season (7.76 ton ha -1 ) was higher than the average grain yield per hectare of maize grown during the rainy season (8.08 ton ha -1 ). These findings follow study findings by Yasin et al [48] and Wicaksana et al [23], which stated that grain yield per hectare of maize grown during the dry season was higher than those grown during the rainy season. The grain yield of maize is highly influenced by air temperature [49,50].…”
Section: Effects Of Genotype × Environment Interactions On Harvest Ag...supporting
confidence: 91%
“…Moreover, testing hybrid maize candidates in several locations and seasons must be done in several locations and seasons to determine a variety that is stable in all environments and specifically stable in specific environments [21,22]. Genotype-byenvironment interactions in multilocation research studies are caused by unpredictable macro-and micro-environment effects such as temperature, Rainfall, and humidity [23]; thus, the tested genotypes will respond differently in each growth environment [24,25].…”
Section: Introductionmentioning
confidence: 99%
“…Similarly, Karuniawan et al, [31] used numerical measurements, AMMI, and GGE biplot to select stable sweet potatoes in West Java, Indonesia. Several other studies also reported the relative contribution of these various measurements to identify the ideal line, including on barley [43], on maize [44,45], on safower [46], on stevia [47], and soybean [48,49]. From our test results, there were four new soybean lines that were identifed as stable and highyielding by various stability measurements, namely A-5A-PSJ (S2), DB-96-CTY (S5), UP 161 (S6), and UP 162 (S7).…”
Section: Discussionmentioning
confidence: 99%
“…Increasing corn raw material demand is inevitable yearly for food and feed industries (Amzeri, 2018). The corn demand is proportional to increasing population and improving people's purchasing power, so an enhancement in production is a dire need (Kayad et al, 2021;Wicaksana et al, 2022). However, in the last seven years, corn production has decreased to target since 2016 in Indonesia (Directorate General of Food Crops, 2020).…”
Section: Introductionmentioning
confidence: 99%
“…However, both have the same direction by optimizing the genetic combinations to support yield (Fromme et al, 2019;Farid et al, 2022). The current development of hybrid cultivars prioritizing heterosis has dominated the concept of optimizing the genetic base (Wicaksana et al, 2022;Bahtiar et al, 2023). However, freepollinating cultivars with specific environments can still show their genetic potential for significant share and support in national corn production (Kutka, 2011;Wolde et al, 2018).…”
Section: Introductionmentioning
confidence: 99%